Assessment of Long-Term Thermal Aging Effects on PVC/Al2O3 Nanocomposites Through Electrical, SEM and FTIR Characterizations - Amraoui, Sabrina; Hedir, Abdallah; Moudoud, Mustapha; Durmus, Ali; Rondot, Sébastien; Haddad, Abderrahmane Manu; Clark, David; Amraoui, Sabrina; Hedir, Abdallah; Moudoud, Mustapha; Durmus, Ali; Rondot, Sébastien; et al. (Energies, 2025)
This study investigated the effect of nanofiller on the structural properties of thermally aged polyvinyl chloride (PVC)/Aluminum oxide (Al2O3) nanoco...
Company: Multidisciplinary Digital Publishing Institute Distributor: Multidisciplinary Digital Publishing Institute Institution: Multidisciplinary Digital Publishing Institute Label: Multidisciplinary Digital Publishing Institute
Keywords: FTIR; SEM; dielectric characterization; nanoparticles; polyvinyl chloride (PVC)/aluminum oxide (Al2O3)